2019
DOI: 10.1186/s13034-019-0271-6
|View full text |Cite
|
Sign up to set email alerts
|

The bumpy road to change: a retrospective qualitative study on formerly detained adolescents’ trajectories towards better lives

Abstract: Background Currently, the risk-oriented focus in forensic youth care is increasingly complemented by a growing interest in strengths-based approaches. Knowledge on how detention and the subsequent period in the community is experienced by adolescents, and which elements are helpful in achieving better lives can contribute to this emerging field. The current study aimed to retrospectively explore adolescents’ experiences from the moment they were detained until 6 to 12 months after they left the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 46 publications
2
10
0
Order By: Relevance
“…In Project Life [33], based on a recovery-oriented peer run course for adults [34], young vulnerable people are challenged to discover their own strengths, possibilities, and future perspectives. Having a clear future perspective seemed to be an important motivation for adolescents to change their former harmful lifestyle [35]. In addition, for peer-rejected young adults with an autism spectrum disorder (Class 3) who have few risk factors before admission and appear to have a lower risk for problems in their young adulthood than young adults in the other classes, treatment should focus primarily on their psychopathology.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Project Life [33], based on a recovery-oriented peer run course for adults [34], young vulnerable people are challenged to discover their own strengths, possibilities, and future perspectives. Having a clear future perspective seemed to be an important motivation for adolescents to change their former harmful lifestyle [35]. In addition, for peer-rejected young adults with an autism spectrum disorder (Class 3) who have few risk factors before admission and appear to have a lower risk for problems in their young adulthood than young adults in the other classes, treatment should focus primarily on their psychopathology.…”
Section: Discussionmentioning
confidence: 99%
“…For young adults in this class, the innovative communication and reflection tool Brain Blocks [36] can be used to improve social-emotional skills by restoring communication between adolescents and their environment. The importance of good communication during treatment, or feeling closely connected to and supported by staff members and other adolescents, is highlighted in a qualitative study from a client-centred perspective in which adolescents described warm human contact as the most important aspect during stay to achieving a better life [35]. Overall, the findings of this exploratory follow-up study indicate that residential care should, for every person, focus (more) on (the prevention of) financial problems, since debt is a substantial problem after discharge and young adults felt less satisfied with their financial situation.…”
Section: Discussionmentioning
confidence: 99%
“…It might be that adolescents interpreted the global wellbeing items as the short-term emotional evaluation of their current situation ("how satisfied are you with your life as a whole at the moment?"). As admission to a closed institution can be considered a stressful life event (Kroll et al, 2002;Van Hecke et al, 2019), it is likely to influence adolescents' general feeling of wellbeing in the initial phase of detention, whereas one's satisfaction on different life domains might be less susceptible to a general feeling of discomfort. Moreover, studies have indicated that QoL is mainly determined by one's subjective appraisal of his/her life, rather than by objective conditions or circumstances (Buitenweg et al, 2018;Jasovic-Gasic et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…This is in line with findings by Harder et al (2011) who demonstrated high prevalence figures of problems in the year following discharge from secure residential care, especially with regard to finances, school and employment, and living arrangements. In the same vein, studies indicate that the process of moving away from a criminal lifestyle, and towards a more prosocial life, is often characterized by a difficult period, in which loss—either with regard to one’s previous identity, daily activities or social networks—plays a central role, and sometimes leads to relapses in old harmful behavior (Van Hecke et al, 2019; Halsey et al, 2017; Nugent & Schinkel, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Available studies on desistance in adolescence refer to the importance of young people’s agency (rational choice); structural aspects (external factors); and the interaction between both (McMahon & Jump, 2018). According to Van Hecke et al (2019, p. 2), desistance can be “operationalized as a certain form of “improvement” or “sense of progress in life” (Aga et al, 2017) as perceived and experienced by adolescents themselves in their daily lives and in relation to their context and the broader society.”…”
Section: Introductionmentioning
confidence: 99%